On paper : the everything of its two-thousand-year history - Basbanes, Nicholas A., 1943- (New York : Vintage Books, a division of Random House LLC, 2014)
Presents a history of paper that traces its invention in China 1,800 years ago through its myriad applications in business, trade, and culture to illuminate paper's crucial role in political scandals, laws, and significant events.
Includes bibliographical references (pages 377-410) and index.
Keywords: Paper -- History; Papermaking -- History; Paper industry -- History; Paper -- History; Papermaking -- History; Paper industry -- History